(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study focuses on transforming military security in the context of globalization, technological advances, and emerging threats. The concept of “military security” reflects the complex and dynamic nature of the contemporary global security environment, which has evolved from the traditional protection of territorial borders and populations to integrated strategies encompassing new threats, such as cyberattacks and hybrid conflicts. The study examines five key factors shaping new approaches to military security: technological advances, geopolitical dynamics, emerging threats, societal changes, and the need for adaptive and comprehensive solutions. It concludes by emphasizing that contemporary military security requires innovative and global approaches to address the challenges of a dynamically changing world.